Scaling up climate advisories in Senegal and Colombia - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
In Senegal, CCAFS has worked closely with the National Meteorological Agency (ANACIM) to develop downscaled climate information services, and enhance the capacity of partners who are tasked to undertake longer-term analysis and communicate information to farmers. Climate information includes details regarding the amount of precipitation and timing of the rainy seasons, as well as daily and 10-day forecasts throughout the rainy season. The project has been piloted since 2011, and the scope has now been widened through a partnership with L’Union des Radios Associatives et Communautaires (URAC), a local union of community radio stations focused on promoting economic development. An estimated 560,000 rural households now have access to climate information services in Senegal. Partnering with URACS gives substantial access to local farmers, as it spans across all 14 administrative regions and operates in local languages, and utilizes an interactive format to engage listeners.